An Analysis of Slang Words in Facebook Used By Eleven Grade Students at SMAN 12 Pandeglang - Kholifah, Nur; Novari, Ari Fajria; Riandi, Riandi (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2024)
The researcher used a qualitative descriptive method with a data collection technique in the form of a questionnaire through student worksheets. The results of the study showed that there were a total of 18 (eighteen) slang words commonly used by students in grades XI.5 and XI.7 of SMAN 12 Pandeglang. In grade XI.5, there were a total of ten slang words. Seven of the data were included in the category of slang patterns in the form of words, three data in the slang pattern in the form of abbreviations. No data was found for the type of slang pattern in numbers, phrases, and in sentences. Then in grade XI.7, a total of eight slang words were found. Two of them were slang patterns in the form of words, six data were found in the slang pattern in the form of abbreviations. No data was found for the type of slang pattern in numbers, phrases, and slang patterns in sentences. The positive impact of using this slang language is that students become more creative. Regardless of whether this slang language is disturbing or not, as long as it is used in the right situation, the right media, and the right communicator. The use of slang can also make it difficult for language users to use it properly and correctly. The use of slang on Facebook is very dynamic, because every student has the creativity and ability to create a new slang word. Therefore, research on slang can continue to be carried out from time to time as a sign that language tends to change.